2004
DOI: 10.1061/(asce)0733-9372(2004)130:4(442)
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrokinetic Remediation of Heavy Metals in Glacial Till Soils Using Different Electrolyte Solutions

Abstract: Previous electrokinetic remediation studies involving the geochemical characterization of heavy metals in high acid buffering soils, such as glacial till soil, revealed significant hexavalent chromium migration towards the anode. The migration of cationic contaminants, such as nickel and cadmium, towards the cathode was insignificant due to their precipitation under the high pH conditions that result when the soil has a high acid buffering capacity. Therefore the present laboratory study was undertaken to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 21 publications
4
38
1
Order By: Relevance
“…Even though Cr is mainly removed to the anode side in these experiments (table 4), the concentration profiles clearly show that transport towards the cathode also takes place. Migration of Cr(III) towards the cathode has also been found in previous works (Buchireddy et al, 2009;Reddy and Chintamreddy, 2004) in parallel with decreasing pH. In our experiments the original soil pH is 7-7.8, and final values are 8-9, so no acidification occurs.…”
Section: Heavy Metal Profiles In the Soil And In Soil Solutionsupporting
confidence: 62%
See 1 more Smart Citation
“…Even though Cr is mainly removed to the anode side in these experiments (table 4), the concentration profiles clearly show that transport towards the cathode also takes place. Migration of Cr(III) towards the cathode has also been found in previous works (Buchireddy et al, 2009;Reddy and Chintamreddy, 2004) in parallel with decreasing pH. In our experiments the original soil pH is 7-7.8, and final values are 8-9, so no acidification occurs.…”
Section: Heavy Metal Profiles In the Soil And In Soil Solutionsupporting
confidence: 62%
“…Removals are nevertheless the highest reported in the literature so far, for a real Cu and Cr-contaminated calcareous soil (Ottosen et al, 2005b). Buchireddy et al (2009) and (Reddy and Chintamreddy, 2004) report higher Cr-removals (72% and 46-82%, respectively) with an artificially spiked soil, but these cannot be compared with our results, where contamination dates back to the 1960's . These results are encouraging and highlight the potential of EDR to remediate soils which are contaminated with a mixture of heavy metals at a neutral pH by choosing a good enhancement solution.…”
Section: Heavy Metal Profiles In the Soil And In Soil Solutioncontrasting
confidence: 55%
“…However, these are only temporary solutions. Recently, electrokinetic (EK) treatment has been used as a method to remediate or control various contaminated media such as soils (Kim et al 2009a(Kim et al , 2009bOttosen et al 2006;Reddy and Chinthamreddy 2004;Reddy et al 2001;Ryu et al 2010;Zhou et al 2004), mine tailings Hansen et al 2005;Kim et al 2002a;Ryu et al 2009), and sludge (Kim et al 2002b;Park et al 2010). The major mechanisms responsible for the removal of contaminants in the EK treatment process are electromigration and electroosmosis (Acar and Alshawabkeh 1993;Acar et al 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Faradic reaction will also occur on the surface of clay particles where DDL will become micro-"anode" and "cathode" so oxidation-reduction process can occur. The higher the concentration of electrolyte, the greater the possibility of oxidation process happen Cameselle, 2015;Reddy and Chinthamreddy, 2004;Yeung and Gu, 2011).…”
Section: Figmentioning
confidence: 99%
“…This biodegradation occurs on clay surface and corresponds to electrokinetic transformation process. Several researchers have suggested that the application of electric fields can increase the production of ATP in order to improve the performance of cells in consuming hydrocarbon compounds (Reddy and Chinthamreddy, 2004;Yeung and Gu, 2011).…”
Section: Biodegradationmentioning
confidence: 99%